A long and winding road: mapping translated literature in 20th-century Portugal - Rosa, Alexandra Assis, 1967- (2012)
This paper profiles the research project Intercultural Literature in Portugal 1930-2000: A Critical Bibliography initiated in 2007 and jointly organized by the University of Lisbon Centre for English Studies (ULICES) and the Centre for Communication and Culture, Catholic University of Lisbon (CECC). The first part of this paper describes (a) the initial project of creating a database of bibliographical records for translated literature 1930-2000, based on three main sources (the Boletim de Bibliografia Portuguesa, the Index Translationum and several catalogues by booksellers and private libraries) to be published in volume form, as well as the process of selecting data considered potentially relevant for researchers in Translation Studies; and (b) how this project developed into a more extensive search for other bibliographical records based on the initial sources, into a verification of all volumes corresponding to each entry at the National Library of Portugal and into an electronic database to be made available online. The second part of this paper discusses a selection of problems met by such an endeavor, the main benefits brought about by offering this online resource, and further research suggested by both problems and information so far identified by this project.